Persistência de anticorpos protetores após sete anos de imunização contra hepatite b em lactentes em Goiânia – GO - Oliveira, Laura Ferreira (2015)
To assess the persistence of anti-HBs protective titers after seven years of primary immunization in children who received the first dose of the Brazilian vaccine against Hepatitis B within the first 12 hours of life and who achieved protective titers after 30-45 days of vaccination (GMT = 491.78 mIU / mL), blood samples were collected between 2014 and 2015 in 147 children. Concurrently held evaluating the persistence of protective titers correlate the application site of VLC vaccine (vastu lateral thigh) or VG (ventrogluteal). Was found that 66,2% of these had no protective titers of anti-HBs, presenting GMT = 6.75 mIU / mL. A positive correlation was found between high levels of anti-HBs after primary vaccination and after seven years (rho Spearman = 0.446, p = <0.0001). None of the participants was positive for anti-HBc marker. When compared to the presence of protective titers between the two vaccine sites of application, there wasn't difference between the two groups (p = 0.756). Keywords: hepatitis B; Anti-hepatitis B antibodies; Immunization; Intramuscular injections.